Incidence, Mortality, Sex Differences, and Demographic Projections for Six Selected Head and Neck Cancer Site Groups in Indonesia: A Secondary Analysis of GLOBOCAN 2024 Modeled Estimates - Lisye Tiur Simanjuntak; Ayesh Mahmood (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Nationally representative data on the heterogeneous malignancies managed in head and neck oncology remain limited in Indonesia. Objective: To estimate incidence, mortality, sex differences, and demographic change for six selected head and neck cancer site groups in Indonesia. Methods: We performed a descriptive secondary analysis of GLOBOCAN 2024 aggregate modeled estimates (version 08 July 2026). The definition included lip and oral cavity (C00–C06), salivary glands (C07–C08), oropharynx (C09–C10), nasopharynx (C11), hypopharynx (C12–C13), and larynx (C32). Counts and age-standardized rates were aggregated across mutually exclusive sites. Indonesia was compared descriptively with four reference populations. Constant-rate Cancer Tomorrow projections and two definitional sensitivity analyses were evaluated. Source uncertainty distributions were unavailable; therefore, confidence intervals were not constructed. Results: An estimated 28,226 cases and 16,025 deaths occurred in 2024; summed ASIR and ASMR were 8.91 and 5.06 per 100,000. Nasopharyngeal cancer contributed 16,064 cases (56.9%) and 8,718 deaths (54.4%). Male rates exceeded female rates: ASIR 13.19 versus 5.18 and ASMR 7.73 versus 2.77. With 2024 rates held constant, annual cases increased to 46,895 (+66.1%) and deaths to 27,900 (+74.1%) by 2050. All 21 validation checks passed. Conclusion: Indonesia's selected head and neck cancer burden is dominated by nasopharyngeal cancer and higher male rates. These modeled estimates support prevention, registry strengthening, and planning hypotheses but do not measure stage, utilization, treatment need, survival, cost, or causal effects.